Studi Penjadwalan dan Pembiayaan Proyek Trashlog PLTA Orya Genyem Kecamatan Unurum Guay Kabupaten Jayapura Menggunakan Microsoft Project Manager 2016 - Abdullah, Raya; Marsudi, Suwanto; Cahya, Evi Nur (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Successful of a project can be seen from how economical and efficient of the project. Minimizing unnecessary expenses to achieve the profits which planned is the goal of this study. The implementation of the Microsoft Project Manager 2016 program aims to assist in scheduling and financing to achieve efficient projects in terms of cost, labor and time. The 3 alternatives used include analysis of heavy equipment productivity, project duration, labor resource requirement, analysis unit cost of work, cost budget plan and s curve. The preparation of this thesis aims to find out the efficiency of the three alternatives reviewed in terms of cost and time project worked. Which results will be different on each alternative. Alternative 1 (90 days with 8 hours/day, total project cost Rp. 7,184,379,188.80), Alternative 2 (90 days with 11 hours/day, total project cost Rp. 7,355,870,347.94) and Alternative 3 (96 days with 8 hours/day, total project cost Rp. 7,019,783,796.95). In terms of cost and time of the three alternatives, can concluded if setting the right number of days and hours of work can be an efficient alternative.